2009
DOI: 10.2174/1874070700903010096
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Food Coloring Agents on DNA Damage Using RAPD Markers

Abstract: Abstract:In this study, faba bean (Vicia faba) seedlings were used as bioindicator to determine genotoxic effect of synthetic dyes currently used as food color additives in many countries. Novel short-term assays are required to substantiate the battery of assessment methods for evaluating the genotoxicity of candidate substances. Therefore, an attempt has been made to evaluate randomly amplified polymorphic DNA (RAPD) analysis for its potential to establish genotoxic effect of colored food. For the preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The study of the carcinogenic and genotoxic effects of food dyes was established by some authors which gives variable results in various systems, DNA damage induced by tartrazine in rat by Himri et al (2012) and Hassan (2010), Gomes et al (2013) and Ventura-Camargo et al (2011) in Allium cepa L., AbdelMigid (2009) in Vicia faba L. and Das and Mukharjee (2004) in Salmonella. All of these studies support the data obtained in the present study and confirms the genotoxic potential of these dyes in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…The study of the carcinogenic and genotoxic effects of food dyes was established by some authors which gives variable results in various systems, DNA damage induced by tartrazine in rat by Himri et al (2012) and Hassan (2010), Gomes et al (2013) and Ventura-Camargo et al (2011) in Allium cepa L., AbdelMigid (2009) in Vicia faba L. and Das and Mukharjee (2004) in Salmonella. All of these studies support the data obtained in the present study and confirms the genotoxic potential of these dyes in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in RAPD profiles could also be used to estimate reduction in root growth, total soluble protein and chlorophyll content (Cenkci et al 2010). As a result of structural changes or mutations in DNA (e.g., rearrangements, point mutations, small inserts or deletions of DNA, and ploidy changes), new sites become accessible to primers, and they can amplify new PCR products (Abdelmigid 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that random amplified polymorphic DNA (RAPD) is a reliable, sensitive and useful biomarker technique for detection of genotoxic effects of many tested substances such as chemical mutagens (Rocco et al, 2014), environmental pollutants (Cansaran-Duman et al, 2014), heavy metals (Do gan et al, 2015;Enan, 2006;Kumar et al, 2015), UV radiation (Kumar et al, 2004), X-ray (Atienzar et al, 2000) and food additives (Abdelmigid, 2009;Shalaby et al, 2014) in the field of genotoxicology. The alterations in RAPD patterns following treatment include appearance of new bands, loss of normal bands and variation in band intensity (Abdelmigid, 2009;Lalrotluanga et al, 2011).…”
Section: Dear Editormentioning
confidence: 99%
“…The alterations in RAPD patterns following treatment include appearance of new bands, loss of normal bands and variation in band intensity (Abdelmigid, 2009;Lalrotluanga et al, 2011). Althought it is not an OECD test guideline, a comparison between untreated and treated genomes shows that RAPD assay is a useful test at molecular level for investigating the specific effects of agents interacting with DNA (Abdelmigid, 2009;Kumar et al, 2015). Some other references and using areas were also given in our manuscript.…”
Section: Dear Editormentioning
confidence: 99%